1999
DOI: 10.1159/000014570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Near-Ultraviolet (UV-A) Light on Melatonin Biosynthesis in Vertebrate Pineal Gland

Abstract: The effects of near-ultraviolet (UV-A) irradiation on nocturnal activity of serotonin N-acetyltransferase (NAT; a key regulatory enzyme in melatonin biosynthesis) in the pineal gland of the rat and chick were investigated. Exposure of the animals to UV-A during the 4th or 5th hour of the dark phase of the 12:12 h light-dark (LD) cycle suppressed the night-driven NAT activity in a time-dependent manner, the effects being generally more pronounced in rats than in chicks. The UV-A-evoked suppression of the noctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The ecological role of the OPN1sw1 opsin in birds is not well understood, but is likely to be broad, as it has been associated with coloration pattern recognition [ 19 ], social signaling, hunting, nectar localization and mate-choice [ 6 8 ]. Others also suggest a role in non-visual processes such as circadian rhythm regulation [ 40 , 41 ]. Species in six avian orders, Pteroclidiformes, Charadriiformes, Coraciiformes, Trogoniformes, Psittaciformes and Passeriformes, have been shown to possess UVS sensitivity [ 16 ], of which the later four belong to core landbirds.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological role of the OPN1sw1 opsin in birds is not well understood, but is likely to be broad, as it has been associated with coloration pattern recognition [ 19 ], social signaling, hunting, nectar localization and mate-choice [ 6 8 ]. Others also suggest a role in non-visual processes such as circadian rhythm regulation [ 40 , 41 ]. Species in six avian orders, Pteroclidiformes, Charadriiformes, Coraciiformes, Trogoniformes, Psittaciformes and Passeriformes, have been shown to possess UVS sensitivity [ 16 ], of which the later four belong to core landbirds.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme N-acetyltransferase, which initiates the conversion of serotonin to melatonin, is reported to be inhibited by UVA radiation. 71,72 This mechanism could theoretically result in increased serotonin production and depletion of circulating melatonin in UV-exposed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of serotonin to melatonin is a photosensitive step resulting from the photoinhibition of the enzymes N-acetyltransferase. It has recently been reported that UVA radiation is a powerful signal affecting the pineal melatonin-generating system and inhibits N-acetyltransferase [ 33 , 38 , 39 ]. Accordingly, it has been observed that melanocytes are photoresponsive cells which express and metabolize indolamines, such as melatonin, during the G 2 phase while responding to UV exposure [ 40 ].…”
Section: Discussionmentioning
confidence: 99%